Placental histopathological features of fetoscopic laser photocoagulation for monoaminotic diamniotic twin pregnancies. (October 2020) - Shiro, Michihisa; Yamamoto, Ryo; Ichikawa, Chihiro; Nakanishi, Kentaro; Kawaguchi, Haruna; Hayashi, Shusaku; Takeuchi, Makoto; Ishii, Keisuke
Abstract: Introduction: This study aimed to compare the histopathological placental features of monochorionic diamniotic (MCDA) twins who did and did not undergo fetoscopic laser photocoagulation (FLP). Methods: This was a retrospective single-institution cohort study on MCDA twins who underwent FLP between October 2010 and December 2018. The control group included MCDA twins who did not undergo FLP and were delivered during the same period in the institute. The incidence of chorioamnionitis (CAM), funisitis, and other pathological findings was compared between the FLP and control groups after matching by gestational age at delivery. Results: In total, 292 MCDA pregnant women who underwent FLP and 356 controls gave birth during the study period. After matching the two groups in the ratio 1:1 by gestational age at delivery, each group comprised 194 subjects. The incidence of histological CAM with Blanc association (stage I, 6.2% vs. 3.1%, crude odds ratio (cOR) = 3.1, P  = 0.052; stage II, 7.2% vs. 5.7%, cOR = 1.6, P  = 0.30; stage III, 2.1% vs. 2.6%, cOR = 0.66, P  = 0.52) and funisitis (artery, 5.2% vs. 3.6%, cOR = 1.3, P  = 0.63; vein 7.2% vs. 4.1%, cOR = 1.6, P  = 0.29) was not statistically significant difference between the FLP and control groups. The FLP group demonstrated a higher incidence of partial placental infarction than the control group (10.3% vs. 3.1%, cOR = 4.3, P  = 0.004, adjusted OR = 2.8, P  = 0.031). Discussion: FLP did not appear to increase the incidence of histological CAM or funisitis in subjects matched by gestational age at delivery. The FLP group demonstrated a higher incidence of partial placental infarction than the control group. Highlights: A retrospective single-institution study on MCDA twins undergoing FLP was performed. FLP did not appear to increase the incidence of histological CAM or funisitis. FLP was associated with a higher incidence of partial placental infarction.